Healthcare Cost and Utilization in Nonalcoholic Fatty Liver Disease: Real‐World Data From a Large U.S. Claims Database. Issue 6 (20th September 2018) - Allen, Alina M.; Van Houten, Holly K.; Sangaralingham, Lindsey R.; Talwalkar, Jayant A.; McCoy, Rozalina G.
Abstract : The prevalence of nonalcoholic fatty liver disease (NAFLD) is increasing. The health care burden resulting from the multidisciplinary management of this complex disease is unknown. We assessed the total health care cost and resource utilization associated with a new NAFLD diagnosis, compared with controls with similar comorbidities. We used OptumLabs Data Warehouse, a large national administrative claims database with longitudinal health data of over 100 million individuals enrolled in private and Medicare Advantage health plans. We identified 152, 064 adults with a first claim for NAFLD between 2010 and 2014, of which 108, 420 were matched 1:1 by age, sex, metabolic comorbidities, length of follow‐up, year of diagnosis, race, geographic region, and insurance type to non‐NAFLD contemporary controls from the OptumLabs Data Warehouse database. Median follow‐up time was 2.6 (range 1‐6.5) years. The final study cohort consisted of 216, 840 people with median age 55 (range 18‐86) years, 53% female, 78% white. The total annual cost of care per NAFLD patient with private insurance was 7, 804 (interquartile range [IQR] 3, 068‐18, 688) for a new diagnosis and 3, 789 (IQR 1, 176‐10, 539) for long‐term management. These costs are significantly higher than the total annual costs of 2, 298 (IQR 681‐6, 580) per matched control with similar metabolic comorbidities but without NAFLD. The largest increases in health care utilization that may account for the increased costs in NAFLD compared with controls are represented by liver biopsies (relative risk [RR] = 55.00, 95% confidence interval [CI] 24.48‐123.59), imaging (RR = 3.95, 95% CI 3.77‐4.15), and hospitalizations (RR = 1.87, 95% CI 1.73‐2.02). Conclusion: The costs associated with the care for NAFLD independent of its metabolic comorbidities are very high, especially at first diagnosis. Research efforts shouldfocus on identification of underlying determinants of use, sources of excess cost, and development of cost‐effective diagnostic tests.